Associations Between Polyvascular Disease and Stroke Recurrence in Patients With Lacunar Stroke - Ma, Lin; Wang, Anxin; Zhang, Yijun; Wang, Yilong; Wang, Yongjun; Meng, Xia (Frontiers in Neurology, 2021)
Background and purpose This study aimed to examine the association of polyvascular disease and clinical outcomes in patients with the stroke subtype of small vessel occlusion (SVO stroke). Methods Data of patients with SVO stroke were collected from The Third China National Stroke Registry. For the present study, polyvascular disease was considered as the existence of coronary heart disease (CHD) and SVO stroke, peripheral arterial disease (PAD) and SVO stroke, and CHD/PAD and SVO stroke. The major clinical outcome was recurrence, and the secondary clinical outcome was major adverse cardiovascular events (MACEs). A Cox proportional multivariable hazards regression model was applied to estimate the association between polyvascular disease and outcomes. Results Among 3165 patients with SVO stroke, CHD was present in 375 (11.8%) and peripheral arterial disease in 168 (5.3%).The hazard ratio (HR) for stroke recurrence was 0.98 (95% confidence interval [CI], 0.65–1.46; p = 0.91) for patients with CHD and SVO stroke, 1.07 (95% CI, 0.61–1.87; p = 0.82) for patients with PAD and SVO stroke, and 0.95 (95% CI, 0.66–1.35; p = 0.75) for patients with CHD/PAD and SVO stroke compared with patients with isolated SVO stroke. The HR for MACEs was 1.01 (95% CI, 0.69–1.49; p = 0.94) for patients with CHD and SVO stroke, 1.11 (95% CI, 0.65–1.90; p = 0.71) for patients with PAD and SVO stroke, and 0.99 (95% CI, 0.70–1.40; p = 0.95) for patients with CHD/PAD and SVO stroke. Conclusion Polyvascular disease is not associated with recurrence of stroke and MACEs in patients with SVO stroke at 1 year.